Small intestinal obstruction in pregnancy and puerperium - Chiedozi Lawrence; Ajabor Linus; Iweze Florentus (The Saudi Journal of Gastroenterology, 1999)
The problem of intestinal obstruction in pregnancy and puerperium is worsened by the risk it poses not just to the mother, but also to the fetus. In this review of 10 pregnant/puerperium patients the maternal mortality was 10% and fetal wastage 20%. In pregnancy and puerperium, intestinal obstruction carries a higher mortality, 10-33%, than in non-pregnant patients, 6-10%. The rarity of the problem, delay in diagnosis, anxiety over radiological examination in pregnant women, worry over laparotomy in pregnant women, all result in delay in instituting definite treatment and contribute to the morbidity. Application of established principles in the management of intestinal obstruction even when it occurs in pregnancy and puerperium might help to improve the results of management and reduce the current level of morbidity and mortality.